Effects of empty chair technique on the resilience of abandoned children - Mendoza, Georgeth T. (College of Education, University of the Philippines Diliman, 2019)
The present study examines the effects of counseling using empty chair on the resilience of abandoned children. Data were collected quantitatively using Connor-Davidson Resilience Scale and quantitatively through interviews among the participants, house parents, social workers, and teachers. These data were further analysed using thematic analysis approach. Finally, based on observation and self-reports, empty chair technique allowed the participants to gain awareness and strengthened their internal coping resources, developed deeper connection with others, able to express feelings regarding parents' abandonment, strengthened their faith in God and gained deeper understanding of integration to broader social world. In this study, the needs of the participants were addressed and resources were identified which can help individuals cope with challenging circumstances.